PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XI MIPA SMA NEGERI 6 PADANG - Hayyu, Mutiara (Jurnal Edukasi dan Penelitian Matematika, 2023)
In school, math communication skills are very important. This study focuses on these skills. The assessment of the XI MIPA class of SMA Negeri 6 Padang shows that students' ability in this area still needs to be improved. Problem-based learning (PBL) can help in this regard. This study examines the advantages of these skills in PBL compared to traditional methods. The study used Quasi Experiment with Posttest-Only Control Group Design and simple random sampling. In the hypothesis test, the P-value of 0.000 rejected the null hypothesis (H0). This shows that PBL outperforms traditional learning.Keywords– Problem Based Learning Model, Mathematical Comuunication Ability, Quasi Experiment